Resistance and Resilience of Hyrcanian Mixed Forests Under Natural and Anthropogenic Disturbances - Vakili, Mehdi; Shakeri, Zahed; Motahari, Saeed; Farahani, Maryam; Robbins, Zachary James; Scheller, Robert M. (Frontiers in Forests and Global Change, 2021)
Biological disturbances are integral to forest ecosystems and have pronounced effects on forest resistance, resilience, and diversity. The Hyrcanian mixed forest, in northern Iran, is at risk of declining resistance, resilience, and diversity due to ongoing pressure from land use change, harvesting, and biological disturbances. We analyzed the resistance and resilience of this area under two biological disturbances (i.e., oak charcoal fungus, Biscogniauxia mediterranea, and alder leaf beetle, Galerucella lineola) and in concert with proposed harvesting. We used a simulation modeling approach whereby we simulated 12 combinations of biological disturbances and harvesting scenarios using the LANDIS-II landscape change model. We estimated the correlation between forest resistance and resilience and tree species diversity to harvesting and biological disturbance. We analyzed the full species composition and age class for 30 and 100 years after disturbances in order to assess resistance as the change in species composition over time. We considered resilience as the ability to recover from a disturbance back to a similar initial state. Results indicate a positive effect of biological disturbances and harvesting on diversity. Our simulations resulted in a negative relationship between diversity-resistance and diversity-resilience within high diversity areas. Our simulation of the Hyrcanian forest reveals that harvesting and biological disturbances, as tested, fulfill the goal of maintaining forest diversity. However, increasing diversity does not always follow by increasing forest resistance and resilience. Scenarios with oak charcoal fungus, both with and without harvesting indicate the lowest decrease in resilient and resistant.